2017
DOI: 10.1021/acs.bioconjchem.7b00496
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Complement Response toward Preclinical and Clinical Nanocarriers in the General Population

Abstract: Opsonization (coating) of nanoparticles with complement C3 component is an important mechanism that triggers immune clearance and downstream anaphylactic and proinflammatory responses. The variability of complement C3 binding to nanoparticles in the general population has not been studied. We examined complement C3 binding to dextran superparamagnetic iron oxide nanoparticles (superparamagnetic iron oxide nanoworms, SPIO NWs, 58 and 110 nm) and clinically approved nanoparticles (carboxymethyl dextran iron oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 45 publications
(106 reference statements)
2
44
0
Order By: Relevance
“…We also found that AmBisome SIs do not match Doxil SIs in the plasma of the same individuals (data not shown). Collectively, this data is in line with earlier studies by Benasutti et al, demonstrating that complement opsonization rates observed with one nanomedicine do not accurately predict complement binding to other structurally similar nanoparticles 22 . Similar to our findings in mouse plasma (Figure 2), individual levels of CFH and CFI varied in plasma of human donors ( Figure 4) and per se could not explain the magnitude of the complement activation by AmBisome.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also found that AmBisome SIs do not match Doxil SIs in the plasma of the same individuals (data not shown). Collectively, this data is in line with earlier studies by Benasutti et al, demonstrating that complement opsonization rates observed with one nanomedicine do not accurately predict complement binding to other structurally similar nanoparticles 22 . Similar to our findings in mouse plasma (Figure 2), individual levels of CFH and CFI varied in plasma of human donors ( Figure 4) and per se could not explain the magnitude of the complement activation by AmBisome.…”
Section: Discussionsupporting
confidence: 89%
“…Another valuable but not broadly used model is a pig 20,21 . Discussions about the advantages and limitations of the in vivo models have also been extensively discussed 8,9,20,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although, PEGylation provides an effective strategy to have stealth and safe nanomedicines, several research papers and clinical reports demonstrate a massive complement activation in patients/animals injected with PEGylated therapeutics. [ 11,39,40 ] In vitro and in vivo experiments demonstrated the complement activation. [ 41 ] In clinical studies, the activation of complement system can result in acute hypersensitivity reactions, or pseudo‐allergic reactions, associated with flushing and/or cutaneous rush, vasoconstrictions and hemodynamic disturbances.…”
Section: Complement System Activationmentioning
confidence: 99%
“…Though it has to be noted that in most cases, a strong complement activation leads to hypersensitivity reactions, interindividual variations in human complement activation responses exist. 41 Apart from the lipid-based formulations, polymeric and inorganic NPs also, such as iron oxide NPs and gadolinium conjugates, were reported to activate the complement system. 30,31,42,43 However, surface-related properties that can have an influence on the complement system activation are more relevant than the category of a nanomaterial, since they determine the PC composition and its subsequent interaction with other plasma proteins including immunoglobulins and components of the complement system 44 (Figure 4).…”
Section: Complement Activationmentioning
confidence: 99%